The Role of Public Relations (PR) in Socially Responsible Business: Analysis of Aqua Danone in Water and Environment Preservation Programs - Rosilawati, Yeni; Ishak, Aswad; Winarsih, Atik (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Corporate Social Responsibility (CSR) encouragesthe company to look further beyond the usual base to a widerregion, which is social at large and communities. This paper aimsto identify the role of Public Relations (PR) in CSR of AquaDanone Klaten in socially responsible business in water andenvironment programs which were implemented in Polan HarjoVillage, the local community that lives around the operating factoryof Aqua. This paper used qualitative approach, specifically usingcase study method. It employed in-depth interviews that wereconducted with the local community and working managers whodeal with CSR issues and strategy on day-to-day basis. Secondarydata was gathered in the form of information about CSR programsfrom regular reports downloaded from the company’s website,mass media news downloaded from the internet and otherresources. The research found that PR process is involved in CSRsteps from fact-finding until monitoring. The study also found thatAqua Danone Klaten carried out proactive dialogue withstakeholders. The planning until the assessment was conductedthrough discussions with community leaders, communities, andlocal governments to give ideas, criticisms, and testimonialstowards CSR programs. The research also identified that PublicRelations (PR) also adopt stakeholder engagement strategy. In thisstrategy, business enterprises prioritize dialogue and engagementwith stakeholders and develop interactive systems with variousstakeholders.